Ca-LDH-modified cementitious coating to enhance corrosion resistance of steel bars. (1st July 2022) - Chen, Mengzhu; Wei, Yanan; Zheng, Haibing; Yu, Linwen; Liu, Qiang; Wang, Yiren; Yuan, Huihui; Wang, Chong; Li, Weihua
Abstract: Layer double hydroxides (LDHs) are potential candidates for the application in reinforced concrete. The main perspective of this paper is to prepare cementitious coatings modified with Ca–Al–NO3 layered double hydroxides (Ca-LDH) and investigate its corrosion inhibition performance on steel bars by means of the isothermal adsorption experiment, open-circuit potential (OCP) and linear polarization resistance (LPR). The effect of Ca-LDH dosage on pore structure and chloride binding ability of cement pastes were studied. The primary aim was to design a novel composite coating applied to reinforced concrete. The results show that the incorporation of Ca-LDH increased the chloride consolidation ability of cement paste. Compared with the uncoated steel bars, the chloride concentration threshold (CCT) of the cement paste coatings with 2% and 4% Ca-LDH increased by 0.07 M and 0.06 M respectively, which effectively inhibited corrosion of steel bars in the simulated concrete pore (SCP) solution with chloride. The incorporation of Ca-LDH into cement paste reduced its porosity and strengthened the physical barrier effect. Moreover, Ca-LDH had the dual ability of consolidating chlorides and releasing corrosion-inhibiting anions. Highlights: a novel composite coating of cementitious coatings modified with Ca-LDH was designed. The inhibition mechanism of Ca-LDH-modified cementitious coating was investigated. Ca-LDH-modified cementitious coating had a better corrosion inhibition effect in SCP solution. The effect of the co-existing anions in the cement paste on the chloride binding ability was discussed.